2020
DOI: 10.3389/fonc.2020.01068
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Portrait of Lung Adenocarcinoma in Brazilian Patients: Past, Present, and Future of Molecular Profiling in the Clinic

Abstract: Objectives: Approximately 60% of lung adenocarcinomas (LAs) carry mutations that can guide treatment with tyrosine-kinase inhibitors (TKI) and other targeted therapies. Data on activating mutations in EGFR and other tyrosine-kinase receptor (TKR) genes in highly admixed populations, such as that of Brazil, are scarce. In this study, we comprehensively analyzed the actionable alteration profile of LA in Brazilian patients. Materials and Methods: EGFR driver mutation data were collected from a large Brazilian LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Unfortunately, access, affordability, and incorporation strategies remain relevant challenges in the public health care. 26,27 Because of the relatively high prevalence of occult CNS metastasis in patients with stage III or IV NSCLC, it is suggested that brain MRI should be routinely performed in most cases. In symptomatic patients, brain MRI is the standard test, whereas CT scan is an alternative when MRI is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, access, affordability, and incorporation strategies remain relevant challenges in the public health care. 26,27 Because of the relatively high prevalence of occult CNS metastasis in patients with stage III or IV NSCLC, it is suggested that brain MRI should be routinely performed in most cases. In symptomatic patients, brain MRI is the standard test, whereas CT scan is an alternative when MRI is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Although no formal surveys exist, an estimated 70% of all AdC NSCLC cases in Brazil undergo molecular testing. 124,162,163 There are no national outcome or survival statistics, as local data collection is variable or simply not performed across several states. In addition, testing practices vary between centers: several laboratories have adopted reflex testing policies, whereas others approach molecular testing as an on-demand service.…”
Section: Brazilmentioning
confidence: 99%
“…In addition, testing practices vary between centers: several laboratories have adopted reflex testing policies, whereas others approach molecular testing as an on-demand service. Similarly, some laboratories prefer NGS technologies, [162][163][164] sequencing 14-20 genes at one time, 124,162,165 whereas others have adopted strategies to improve TAT by using RT-PCR assays for EGFR and BRAF mutations, 162,[164][165][166] and IHC/FISH for ALK, ROS1 and PD-L1 rearrangements. 163,164,167 In the absence of government reimbursement for molecular testing, several pharmaceutical companies have recently established a national "Lung Mapping" consortium.…”
Section: Brazilmentioning
confidence: 99%
“…All extracted features were classified into three categories include (1) first-order features; (2) shape-and size-based features; (3) textural features. Specifically, the textural features were computed based on four kinds of the matrix: 1) gray-level co-occurrence matrix (GLCM), 2)…”
Section: Radiomic Features Extraction and Selectionmentioning
confidence: 99%
“…[1] In lung adenocarcinoma patients, more than 60% carry driver mutations that could guide treatment strategies and the epidermal growth factor receptor (EGFR) mutation is one of the most frequent genetic alterations among them. [2; 3] EGFR-mutant lung adenocarcinoma patients were proved to be highly sensitive to EGFR-tyrosine kinase inhibitors (TKIs) and achieve significant survival benefit from EGFR-TKIs as the first-line treatment,[4; 5] hence it is much valuable for lung adenocarcinoma patients to confirm the EGFR mutation status in clinical practice, for treatment guidance.…”
Section: Introductionmentioning
confidence: 99%